2019
DOI: 10.3390/cancers11070965
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Cancer Stem Cells in Triple-Negative Breast Cancer

Abstract: Triple-negative breast cancer (TNBC) is a highly aggressive form of breast cancer that lacks targeted therapy options, and patients diagnosed with TNBC have poorer outcomes than patients with other breast cancer subtypes. Emerging evidence suggests that breast cancer stem cells (BCSCs), which have tumor-initiating potential and possess self-renewal capacity, may be responsible for this poor outcome by promoting therapy resistance, metastasis, and recurrence. TNBC cells have been consistently reported to displa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
133
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(135 citation statements)
references
References 160 publications
(210 reference statements)
1
133
0
1
Order By: Relevance
“…MCF7 is ERα+ breast cancer cell line and MDA-MB-468 is triple-negative breast cancer (TNBC) cell line. It has been reported that TNBC cells are more like cancer stem cells (CSC) in terms of gene expression signature 35 .…”
Section: Tnf-α Increases Breast Cancer Stem-like Cells and Up-regulatmentioning
confidence: 99%
“…MCF7 is ERα+ breast cancer cell line and MDA-MB-468 is triple-negative breast cancer (TNBC) cell line. It has been reported that TNBC cells are more like cancer stem cells (CSC) in terms of gene expression signature 35 .…”
Section: Tnf-α Increases Breast Cancer Stem-like Cells and Up-regulatmentioning
confidence: 99%
“…In further connection with TNBC, stemness factors such as SOX2 and Myc are enriched in TNBC [20,21]. In fact, the gene expression signatures of TNBCs exhibited striking similarities to those of mammary stem cells [22]. The developmental Wnt/β-catenin, Notch, and Hedgehog (Hh) pathways are also more active in both CSCs and TNBC [23][24][25].…”
mentioning
confidence: 99%
“…A further shared characteristic of TNBCs and breast CSCs is epithelial-mesenchymal transition (EMT), a phenotypic change in cells and process that contributes to invasion and distant metastasis [26]. EMT-inducing transcription factors are enriched in TNBCs and mesenchymal proteins are upregulated, while epithelial proteins are down-regulated [22]. EMT confers tumor cells with CSC-like characteristics [27,28].…”
mentioning
confidence: 99%
“…In the present study, by exploiting the mechanism of CSCs formation in GC, we identified a specific role of DDIT3 and CEBPβ, which are enriched in the tumour tissues and cells, and further mediated the CSCs stemness in GC. In fact, various studies have shown that CSCs has the ability to self‐renewal, and thereby inducing tumour proliferation, forming spheroids and promoting tumorigenesis [14] . Therefore, CSCs are believed to mediate multidrug resistance, metastasis and poor prognosis.…”
Section: Discussionmentioning
confidence: 99%